Dancing on Ropes ‐ Enantioselective Functionalization of Preformed Four‐Membered Carbocycles. Issue 11 (14th March 2022) - Chen, Jun; Zhou, Qiang; Fang, Huayi; Lu, Ping
Comprehensive Summary: Cyclobutane derivatives have been recognized as useful structural motifs in organic synthesis and drug design. With the revival of photochemistry, the enantioselective synthesis of cyclobutane derivatives using [2 + 2]‐cycloadditions has garnered numerous attentions. On the other hand, enantioselective functionalization of preformed four‐membered carbocycles is emerging as an important complementary approach to access chiral cyclobutane derivatives with versatile structural patterns. Herein, we summarize recent advances in this field from 2012. To avoid undesired C—C bond cleavage driven by strain‐releasing, it is crucial to choose compatible methods for enantioselective functionalization and meanwhile preserving intact four‐membered ring skeleton. Guided by calculated hydrogenation enthalpies, which are used to evaluate the strain energy of indicated C—C bond, a clear picture of the developed methodologies on functionalization of four‐membered carbocycles combining the strain energy and enhanced reactivity is presented. Abstract : Recent advances in enantioselective functionalization of readily available preformed four‐membered carbocycles are summarized in this review. This strategy has been emerging as a general and efficient approach to access enantiomerically enriched cyclobutane derivatives with various structural patterns. DFT calculations have been conducted to better understand correlation between the strain energy (estimated by the hydrogenation enthalpy) and enhanced reactivity.